Alaska Upper Crustal Velocities Revealed by Air-to-Ground Coupled Waves From the 2022 Hunga Tonga-Hunga Ha’apai Eruption - Kenneth Macpherson; David Fee; Stefan Awender; Bryant Chow; Juliann Colwell; Sam Delamere; Matt Haney (Seismica, 2025)
Pressure changes in the atmosphere couple to the solid earth, producing ground motions that contain information about local crustal elastic parameters. This type of air-to-ground coupled wave was observed globally following the largest explosion of the instrumental age, the climactic eruption of the Hunga Tonga-Hunga Ha’apai volcano on 15th January, 2022. We utilize this unprecedented source, along with the presence of colocated seismometers, infrasound sensors, and barometers in Alaska, to examine coupling and reveal elastic parameters beneath the stations. We derive coupling spectra by forming seismic--to--pressure amplitude ratios as a function of frequency, and identify passbands of high coherence between the pressure and seismic records. By relating coupling spectra in high-coherence bands to elastic parameters, we estimate mean shear wave velocities under stations to a depth encompassing much of the upper crust. Our velocity estimates from low-frequency coupling exhibit good agreement with a previously existing tomographic velocity model from Berg et al. (2020), while estimates from high-frequency coupling show considerable scatter when compared to proxy Vs30, even though the overall values are reasonable. In addition to providing velocity estimates, our results also indicate that, for the broadband pressure signals from the Hunga Tonga-Hunga Ha’apai eruption, microseismic noise exerts a strong effect on the frequency bands where coupling is observed, and that the air-to-ground coupled waves exhibit significant complexity not necessarily described by theory. Our results show that coupling observations provide a simple forward observation of mean seismic velocities beneath seismoacoustic stations, without the need to resort to complex inversion schemes. It is remarkable that pressure waves generated thousands of kilometers away are able to reveal the seismic velocity structure of Alaska to several kilometers depth.